Association between cardiopulmonary exercise capacity and clinical parameters in post-PCI patients with coronary artery disease from Fujian, China - Lin, LiHan; Li, Delong; Liu, YiPing; Hu, GuoPeng; Zheng, Wei; Chen, ZuLin; Zheng, YiKun; Dong, YongDa (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPeak oxygen uptake (VO₂peak) assessed by cardiopulmonary exercise testing (CPET) is a key indicator of functional capacity and prognosis in patients with coronary artery disease (CAD) following percutaneous coronary intervention (PCI). However, the clinical predictors of exercise capacity among post-PCI patients in Fujian, China, remain insufficiently characterized. Identifying such predictors can enhance individualized rehabilitation strategies and secondary prevention measures in clinical practice.MethodsThis retrospective study analyzed 575 CAD patients who underwent PCI and completed CPET within six weeks post-procedure at Quanzhou First Hospital Affiliated to Fujian Medical University from June 2020 to June 2024. Participants' demographics, medical history, echocardiographic parameters, and laboratory results were collected. Univariable and multivariable linear regression identified independent predictors of VO₂peak, with subgroup analyses by age (<65 vs. ≥65 years) and gender.ResultsThe mean VO₂peak of the study population was 19.29 ± 4.41 ml/kg/min. Independent predictors of lower VO₂peak included older age (β = –0.06, P < 0.001), female sex (β = –1.71, P < 0.001), acute coronary syndrome (ACS; β = –1.01, P < 0.001), smoking (β = –2.37, P < 0.001), hypertension (β = –0.82, P = 0.004), higher resting heart rate (RHR; β = –0.10, P < 0.001), and lower hematocrit (HCT; β = –0.20, P = 0.002). Conversely, higher red blood cell (RBC) count (β = 1.20, P = 0.012) and hemoglobin (Hb; β = 0.09, P < 0.001) levels predicted better exercise capacity. Subgroup analyses highlighted age- and sex-specific determinants: notably, lower main pulmonary artery diameter (MPA) and lower HCT uniquely affected younger patients, while hypertension primarily impacted older patients. Gender-specific associations revealed that hypertension and high-density lipoprotein cholesterol (HDL-C) predicted VO₂peak in males, whereas lower body weight, higher RBC, and lower HCT were significant in females.ConclusionSignificant demographic, clinical, echocardiographic, and biochemical predictors of cardiopulmonary exercise capacity were identified among post-PCI CAD patients from Fujian, China. Age- and sex-specific differences underline the necessity for personalized rehabilitation and prevention strategies to improve cardiopulmonary fitness and clinical outcomes in this population.